Effect of Employee Placements, Discipline, and Work Climate toward Employee Performance on Agency of Financial Management and Asset Regional of Lubuklinggau City Indonesia - Jefirstson Richset Riwukore; Yohanes Susanto; Mardiyah Mardiyah; Fellyanus Habaora (Institute of Computer Science (IOCS), 2022)
The research objective was to determine the effect of work placement, discipline and work climate toward employee performance at Agency of Financial Management and Asset Regional of Lubuklinggau City in Indonesia simultaneously and partially (quantitative). The sample in this research were all employees at Agency of Financial Management and Asset Regional of Lubuklinggau City as many as 50 people. The data analysis technique used in this research is multiple linear regression testing, determination coefficient test, F test and t test. The research results obtained are: 1). Partial test (t test) which is performed prove that job placement has an effect to employee performance at Agency of Financial Management and Asset Regional of Lubuklinggau City where is t-value 3,624 > t-table 2,008 and also a sig as many as 0,024 < 0,05; 2). Discipline affects to employee performance at Agency of Financial Management and Asset Regional of Lubuklinggau City, where is t-value 4,061 > t-table 2,008 an also a sig as many as 0,018 < 0,05; 3). Work climate affects toward services at Agency of Financial Management and Asset Regional of Lubuklinggau City, where is t-value 4,661 > t-table 2,008 and also a sig as many as 0,012 < 0,05; 4). Work placement, discipline and work climate significant effect simultaneously to services at Agency of Financial Management and Asset Regional of Lubuklinggau City, where is F-value 6,208 > F-table 2,81 and also a sig as many as 0,006 < 0,05.